ANALISIS RASIO LIKUIDITAS, SOLVABILITAS, AKTIVITAS DAN PROFITABILITAS UNTUK MENILAI KINERJA KEUANGAN PT MARTINA BERTO TBK PERIODE 2014-2018 - Satria Rukmana, Heru; Mariana, Linda (Economicus, 2021)
The results of this study show that the liquidity ratio consisting of current ratio in 2014 was above the industry average and in 2015-2018 was below the industry average, the quick ratio in 2014-2016 was above the industry average and in 2017-2018 was below the industry average, the cash ratio in 2014 was above the industry average and in 2015-2018 was below the industry average. The solvency ratio consisting of debt to asset ratio in 2014 was below the industry average and in 2015-2018 was above the industry average, the debt to equity ratio in 2014 was below the industry average and in 2015-2018 was above the industry average. The ratio of activities consisting of receivable turn over in 2014-2018 is below the industry average, inventory turn over in 2014-2017 was above the industry average and in 2018 was below the industry average, fixed asset turn over in 2014-2018 was below the industry average, fixed asset turn over in 2014-2018 was above the industry average , the total asset turn over in 2014-2018 was below the industry average. The profitability ratio consisting of return on assets in 2014-2018 is below the industry average, return on equity in 2014-2018 is below the industry average and net profit margin in 2014-2018 is below the industry average.